Effectiveness of Yoga for Hypertension: Systematic Review and Meta-Analysis. (28th May 2013) - Hagins, Marshall; States, Rebecca; Selfe, Terry; Innes, Kim
Abstract : Objectives . To systematically review and meta-analyze the effectiveness of yoga for reducing blood pressure in adults with hypertension and to assess the modifying influences of type and length of yoga intervention and type of comparison group. Methods . Academic Search Premier, AltHealthWatch, BIOSIS/Biological Abstracts, CINAHL, Cochrane Library, Embase, MEDLINE, PsycINFO, PsycARTICLES, Natural Standard, and Web of Science databases were screened for controlled studies from 1966 to March 2013. Two authors independently assessed risk of bias using the Cochrane Risk of Bias Tool. Results . All 17 studies included in the review had unclear or high risk of bias. Yoga had a modest but significant effect on systolic blood pressure (SBP) (- 4.17 [- 6.35, - 1.99], P = 0.0002 ) and diastolic blood pressure (DBP) (- 3.62 [- 4.92, - 1.60], P = 0.0001 ). Subgroup analyses demonstrated significant reductions in blood pressure for (1) interventions incorporating 3 basic elements of yoga practice (postures, meditation, and breathing) (SBP: - 8.17 mmHg [- 12.45, - 3.89]; DBP: - 6.14 mmHg [- 9.39, - 2.89]) but not for more limited yoga interventions; (2) yoga compared to no treatment (SBP: - 7.96 mmHg [- 10.65, - 5.27]) but not for exercise. Conclusion . Yoga can be preliminarily recommended as an effective intervention for reducing blood pressure. Additional rigorous controlled trials are warranted to further investigate the potential benefits of yoga.